2010
DOI: 10.1186/1472-6939-11-19
|View full text |Cite
|
Sign up to set email alerts
|

The role of advance directives in end-of-life decisions in Austria: survey of intensive care physicians

Abstract: BackgroundCurrently, intensive care medicine strives to define a generally accepted way of dealing with end-of-life decisions, therapy limitation and therapy discontinuation.In 2006 a new advance directive legislation was enacted in Austria. Patients may now document their personal views regarding extension of treatment. The aim of this survey was to explore Austrian intensive care physicians' experiences with and their acceptance of the new advance directive legislation two years after enactment (2008).Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 17 publications
2
26
1
3
Order By: Relevance
“…These figures are higher than those reported by Schaden et al from intensive care physicians [10] and meet with expectations of the patients [11]. …”
Section: Discussionsupporting
confidence: 82%
“…These figures are higher than those reported by Schaden et al from intensive care physicians [10] and meet with expectations of the patients [11]. …”
Section: Discussionsupporting
confidence: 82%
“…(2010) [ 37 ] Greece To study the frequency, type and rationale for limiting life support in Greek multidisciplinary ICUs, the clinical and demographic parameters associated with limiting life support, and the participation of relatives in the decision-making process Prospective observational study, with an anonymous questionnaire in 8 multidisciplinary, general hospital-affiliated ICUs 304 patients and their physicians 7 Schaden et al . (2010) [ 38 ] Austria To explore Austrian intensive care physicians’ experiences with, and their acceptance of, the new advance directives legislation 2 years after enactment Survey of all ICUs in Austria 139 participants 6 Westphal and McKee (2009) [ 39 ] USA To examine differences between physicians and nurses regarding knowledge about advance directives and do-not-resuscitate orders, and the personal factors that underlie beliefs and practices related to the use of advance directives and do-not-resuscitate orders Survey 53 physicians 6 Sprung et al . (2008) [ 40 ] European countries (17 countries) To evaluate physician documentation and the reasoning, considerations and difficulties in end-of-life decision-making in ICUs Prospective study of end-of-life practices and decisions in consecutive patients who died or were subject to any limitation of life-saving interventions in 37 ICUs in 17 European countries ICU physicians 6 Collins et al .…”
Section: Resultsmentioning
confidence: 99%
“…Physicians are uncertain about the legal standing of, and have no experience with, advance directives (weak evidence) [ 38 ]. Establish and document clear, realistic, and appropriate goals of care in consultation with the patient and family (QI 21) …”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that such conflicts are on the rise in the nursing field, due both to the increasing complexity of care and the scientific and technological advances which have been made in recent decades. In this regard, critical care units are a setting that is especially prone to conflict [1-14]. Various authors have suggested that the ethical conflicts experienced by critical care nurses stem from three main sources: the relationships with patients and their families, the provision of certain treatments and/or the characteristics of the setting in which the clinical team works.…”
Section: Introductionmentioning
confidence: 99%